Hepatitis E Virus and Related Viruses in Animals. Issue 1 (27th April 2015) - Thiry, D.; Mauroy, A.; Pavio, N.; Purdy, M. A.; Rose, N.; Thiry, E.; de Oliveira‐Filho, E. F.
Summary: Hepatitis E is an acute human liver disease in healthy individuals which may eventually become chronic. It is caused by the hepatitis E virus (HEV) and can have a zoonotic origin. Nearly 57, 000 people die yearly from hepatitis E‐related conditions. The disease is endemic in both developing and developed countries with distinct epidemiologic profiles. In developing countries, the disease is associated with inadequate water treatment, while in developed countries, transmission is associated with animal contact and the ingestion of raw or uncooked meat, especially liver. All human HEV are grouped into at least four genotypes, while HEV or HEV‐related viruses have been identified in an increasing number of domestic and wild animal species. Despite a high genetic diversity, only one single HEV serotype has been described to date for HEV genotypes 1–4. The discovery of new HEV or HEV‐related viruses leads to a continuing increase in the number of genotypes. In addition, the genome organization of all these viruses is variable with overlapping open reading frames (ORF) and differences in the location of ORF3. In spite of the role of some domestic and wild animals as reservoir, the origin of HEV and HEV‐related viruses in humans and animals is still unclear. This review discusses aspects of the detection, molecular virology, zoonotic transmission and origin of HEV and HEV‐related viruses in the context of 'One Health' and establishes a link between the previous and the new taxonomy of this growing virus family.